Physiologic predictors of collateral circulation and infarct growth during anesthesia – Detailed analyses of the GOLIATH trial. Issue 6 (June 2020) - Raychev, Radoslav; Liebeskind, David S; Yoo, Albert J; Rasmussen, Mads; Arnaudov, Dimiter; Brown, Scott; Saver, Jeffrey; Simonsen, Claus Z
Collateral circulation plays a pivotal role in acute ischemic stroke due to large vessel occlusion (LVO) and may be affected by multiple variables during sedation for endovascular therapy (EVT). We conducted detailed analyses of the GOLIATH trial to identify predictors of collateral circulation grade and infarct growth. We also modified the ASITN collateral grading scale and sought to determine its impact on clinical outcome and infarct growth. Multivariable analysis was used to identify predictors of collaterals and infarct growth. Ordinal analysis demonstrated nominal, but non-significant association between modified ASITN scale and infarct growth. Among all analyzed baseline clinical and procedural variables, the most significant predictors of infarct growth at 24 h were phenylephrine dose (estimate 6.78; p = 0.014) and baseline infarct volume (estimate 0.93; p = 0.03). The most significant predictors of worse collateral grade were mean arterial pressure (MAP) <70 mmHg (OR 0.35; p = 0.048) and baseline infarct volume (OR 0.96; p = 0.003). Hypotension during sedation for EVT for LVO negatively impacts collateral circulation, while higher pressor dose is a strong predictor of infarct growth. Avoidance of anesthesia-induced hypotension and consequent need for pressor therapy may prevent collateral failure and minimize infarct growth.